THE ANTIMICROBIAL AND ANTIBIOFILM ACTIVITY OF LOCAL WHEAT BRAN EXTRACT AGAINST PATHOGENIC BACTERIA AND YEAST - Abbas , Omer. N.; Majeed, M. R. Majeed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The current study was aimed to investigate the antimicrobial and antibiofilm efficiency of local wheat bran active metabolites over locally isolated pathogens including Escherichia coli, Staphylococcus aureus and Candida albicans. Local wheat Ibaa99 bran extract consists of phenolic compounds, inulin and phytic acid. The antibacterial activity was examined by well diffusion assay and the minimum inhibitory concentration method by the concentration 1mg/ml for Wheat Bran Extract. On the other hand, antibiofilm dispersal consideration have been completed by Microtiter plate method. The results revealed that Ibaa99 wheat bran extract has antimicrobial activity in average diameter zone, highest inhibition observed over C. albicans isolate with 60 ±0.1 mm. Moreover, the minimum inhibitory concentrations of wheat bran extract were 1 mg/ml against both E. coli and S. aureus isolates. The outcomes of biofilms suppression show high reduction in biofilms, the highest dispersal recorded for Candida albicans with OD (0.07). In conclusion, the extract of local wheat bran is a has antimicrobial effect and biofilm suppressor and represent a promising cheap by- product as alternative medication that can be used to treat many gastrointestinal pathogens.